Implications of Corruption Crime in Indonesia and Its Countermeasures - Satibi, Iwan (International Journal of Psychosocial Rehabilitation, 2020)
This article aims to uncover the implications of corruption crime on the lives of the people, nation and state. In addition, this article also explains what is the cause of the increasingly rampant corruption crime and how to overcome it. Through a qualitative approach and desk study method, the results of this study have revealed the magnitude of the implications of corruption crime on the lives of the people, nation and state. Empirical facts show that the increasingly widespread corruption case is actually a "tragedy" that can functionally destroy the life order of a nation due to the cunning and deception of corruptors who have undermined all the nation's resources and potential. This study then concluded that the implications of corruption crime, in plain view had a very extraordinary impact both on social, economic, cultural and even national resilience.